Implementation and evaluation of an a psychosocial educational programme to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide - Sumpi, Ndempavali; Amukugo, Hans Justus (International Journal of Health, 2016)
This paper focuses on the process of the implementation and evaluation of a psychosocial training programme to facilitate reintegration of the imprisoned women who have dumped babies and / or committed infanticide. This paper consists of two sections. The first section deals with the implementation of the psychosocial training programme while the second section evaluates the implementation and the outcomes evaluation of the of the programme. The programme was completed during a three-day workshop at the Correctional Facility in Namibia.